Pemilihan pengajar berkesan menggunakan kaedah proses hierarki analisis kabur - Wan Rosmanira Ismail ,; Ummul Khair Salma Din ,; Witriany Basri , (Penerbit ukm, 2005)
This study is carried out to explore the method of selecting a lecturer with the most effective teaching skill. The method that has been identified is Fuzzy Analytical Hierarchy Process (AHP). The selection by students using this method is more reliable compared to the existing one, which uses the average score given by students. This is because Fuzzy AHP takes into account the relative comparison between lecturers as well as includes the degree of importance given by students in each of the factors that contribute to effective teaching. Fuzzy numbers are used in the pair wise comparison in order to alleviate the problem of inflexibility in the process of choosing the lecturer with the most effective teaching skill